2008
DOI: 10.1183/09031936.00093908
|View full text |Cite
|
Sign up to set email alerts
|

Lung cancer gene associated with COPD: triple whammy or possible confounding effect?

Abstract: Recently, several large genome-wide association studies have identified a putative ''lung cancer'' locus in the nicotinic acetylcholine receptor subunit genes (nAChR) on 15q25. However, these findings may be confounded by the presence of chronic obstructive pulmonary disease (COPD), which is also strongly associated with smoking exposure and lung cancer. This is likely as the prevalence of COPD in lung cancer cohorts is as much as two-fold greater than that reported in smoking control populations (50 versus 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
124
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(134 citation statements)
references
References 35 publications
7
124
0
3
Order By: Relevance
“…However, the results of many small candidate gene studies have been inconsistent (9,10). Genomewide association studies (GWASs) of COPD (11)(12)(13) have, to date, identified three susceptibility loci that have been well replicated (14)(15)(16)(17)(18)(19)(20)(21). We report the results of a follow-up GWAS in four cohorts that identifiy a new COPD susceptibility locus.…”
Section: Introductionmentioning
confidence: 98%
“…However, the results of many small candidate gene studies have been inconsistent (9,10). Genomewide association studies (GWASs) of COPD (11)(12)(13) have, to date, identified three susceptibility loci that have been well replicated (14)(15)(16)(17)(18)(19)(20)(21). We report the results of a follow-up GWAS in four cohorts that identifiy a new COPD susceptibility locus.…”
Section: Introductionmentioning
confidence: 98%
“…The observation could be explained by possible pathologic relations between COPD and lung cancer (24,25). Recent genetic linkage studies have identified common, biologically potential genetic markers in families who have susceptibility for both COPD and lung cancer (25). Therefore, discrimination of NSCLC from the benign disease has presented a difficult problem in past studies, in which a relatively high percentage of false-positive classification of NSCLC was observed.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, we found that these lung cancer-associated genetic changes were also related to COPD. The observation could be explained by possible pathologic relations between COPD and lung cancer (24,25). Recent genetic linkage studies have identified common, biologically potential genetic markers in families who have susceptibility for both COPD and lung cancer (25).…”
Section: Discussionmentioning
confidence: 99%
“…There is currently much interest in genetic markers in the 15q25 locus, encompassing the cluster of nicotinic cholinergic receptor genes CHRNA3/CHRNA5/CHRNB4, which have been associated with chronic obstructive pulmonary disease (COPD) and smoking behavior. 3,8 It has been speculated that functional variants in this region may actually be primarily influencing nicotine addiction, as observed in recent GWASs on smoking intensity, and are thus only associated with COPD due to the well-known links between smoking and COPD. [9][10][11] To determine if the genetic marker influences COPD through pathways other than smoking, the COPD case-control binary variable has the role of target phenotype 'T' , smoking, represented as cumulative exposure to tobacco smoke (ie pack-years smoked) or number of cigarettes smoked per day, has the role of secondary phenotype 'K' , the well-known diagnostic criteria for smoking, such as gender, has the role of variable 'L' .…”
Section: Methodsmentioning
confidence: 99%